2015
DOI: 10.1002/bies.201400171
|View full text |Cite
|
Sign up to set email alerts
|

Do wild carnivores forage for prey or for nutrients?

Abstract: A widespread perception is that carnivores are limited by the amount of prey that can be captured rather than their nutritional quality, and thus have no need to regulate macronutrient balance. Contrary to this view, recent laboratory studies show macronutrient-specific food selection by both invertebrate and vertebrate predators, and in some cases also associated performance benefits. The question thus arises of whether wild predators might likewise feed selectively according to the macronutrient content of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 105 publications
1
86
0
3
Order By: Relevance
“…The observation that tangle‐web spiders have higher C content than their prey provides support to the hypothesis that predators may suffer from C (i.e., energy) limitation (Wilder et al., 2013). Recent empirical research suggests that energy limitation may be common for some predatory species such as ants, beetles, and spiders (Grover, Kay, Monson, Marsh, & Holway, 2007; Kohl, Coogan, & Raubenheimer, 2015; Noreika, Madsen, Jensen, & Toft, 2016; Wilder et al., 2013; Wiggins & Wilder, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…The observation that tangle‐web spiders have higher C content than their prey provides support to the hypothesis that predators may suffer from C (i.e., energy) limitation (Wilder et al., 2013). Recent empirical research suggests that energy limitation may be common for some predatory species such as ants, beetles, and spiders (Grover, Kay, Monson, Marsh, & Holway, 2007; Kohl, Coogan, & Raubenheimer, 2015; Noreika, Madsen, Jensen, & Toft, 2016; Wilder et al., 2013; Wiggins & Wilder, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…This diet preference of dogs contrasts that of domestic cats, which selected diets highest in protein energy (Hewson-Hughes et al 2013, Kohl et al 2015. If wolves and cougars are selecting diets that optimize their macronutrient intake, then these differences in nutrient selection between species might explain the higher proportion of livestock killed by wolves as compared to cougars, both in our study and around the world (Newsome et al 2015).…”
Section: Discussionmentioning
confidence: 55%
“…Macronutrient requirements might also play a role in carnivore predation on livestock; in a laboratory setting domestic dogs selected a diet lower in protein but higher in lipids (Kohl et al 2015), and meat from domestic livestock is typically higher in lipid content than meat from wild prey (Eaton and Konner 1985, Davidson et al 2011, Coogan and Raubenheimer 2016. This diet preference of dogs contrasts that of domestic cats, which selected diets highest in protein energy (Hewson-Hughes et al 2013, Kohl et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in the role that nutrients play in prey selection by predators (Mayntz et al 2005;Kohl et al 2015), catalysed by the development of the nutritional geometry framework (Raubenheimer & Simpson 1997;Raubenheimer 2011). This framework considers how mixtures of nutrients might affect food choice and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using this approach have shown that many species of herbivores and omnivores, both in the lab and the field, choose foods and regulate the amounts eaten based on macronutrient (protein, lipid and carbohydrate) balance rather than energy content per se (Simpson & Raubenheimer 2012). Recent evidence suggests that some predators, including insects, spiders, fish, mink and bears, likewise select prey (or selectively eat certain body parts of prey) based on a requirement for a specific balance of macronutrients (reviewed in Kohl et al 2015). However, few studies have applied this framework to examine prey choice of predators in the field (Machovsky-Capuska et al 2016).…”
Section: Introductionmentioning
confidence: 99%